Β‐cyclodextrin‐ionic liquid polymer based dynamically coating for simultaneous determination of tetracyclines by capillary electrophoresis. Issue 7 (17th January 2017) - Zhou, Chunyan; Deng, Jingjing; Shi, Guoyue; Zhou, Tianshu
Abstract : Tetracyclines are a group of broad spectrum antibiotics widely used in animal husbandry to prevent and treat diseases. However, the improper use of tetracyclines may result in the presence of their residues in animal tissues or waste. Recently, great attention has been drawn towards the green solvents ionic liquids. Ionic liquids have been employed as a coating material to modify the electroosmotic flow in capillary electrophoresis. In this study, a functionalized ionic liquid, mono‐6‐deoxy‐6‐(3‐methylimidazolium)‐β‐cyclodextrin tosylate, was synthesized and used for the simultaneous separation and quantification of tetracyclines by capillary electrophoresis. Good separation efficiency could be achieved due to the multiple functions of β‐cyclodextrin derived ionic liquid, including the electrostatic interaction, the hydrogen bonding, and the cavity structure in β‐cyclodextrin ionic liquid which can entrap the tetracyclines to form inclusion complex. After optimization, baseline separation achieved in 25 min with the running buffer consisted of 10 mmol/L, pH 7.2 phosphate buffer and 20 mmol/L β‐cyclodextrin ionic liquid. The satisfied result demonstrated that the β‐cyclodextrin ionic liquid is an ideal background electrolyte modifier in the separation of tetracyclines with high stability and good reproducibility. And it is an effective strategy to design and synthesize specific ILs as additive applied in separation.